HIGH POLITICS MUHAMMADIYAH - Marratu Fahri (PRAJA: Jurnal Ilmiah Pemerintahan, 2023)
After the reform, many fundamental changes regarding the rights and obligations of the people underwent redefinition. Previously, very few political rights were enjoyed by the people. In the midst of reform, it seemed as if the people were allowed to determine their own political rights, but the awareness of their obligations actually receded. Such an open political condition allows many parties to form political parties, the people have broad political channels through various platforms. Likewise, Mass Organizations and NGOs of various forms grow like mushrooms in the rainy season. Some of them even go beyond their roles and functions to a certain extent, as if they have become a formal political institution like a political party or at least become a "certifier/stamp", a certain political force. Some circles really want Muhammadiyah not to be "ignorant" or "shy", taking advantage of such an opportunity and momentum. However, Muhammadiyah has remained consistent as a religious mass organization that prioritizes national politics or high politics even though it has had contact with political parties, as a special member of Masjumi and gave birth to Parmusi and even in the reform era it is considered to have contributed to the founding of the National Mandate Party. However, Muhmmadiyah has never turned into a political party and consistently maintains the core of Muhammadiyah as an Islamic da'wah movement that works in the field of human and social life, has no organizational relationship with and is not affiliated with any political party or organization. Every member of Muhammadiyah according to their human rights, may not enter or enter other organizations, as long as they do not deviate from the AD/ART, and other provisions that apply in the association.